Structural Origin of Metal Specificity in Isatin Hydrolase from Labrenzia aggregata Investigated by Computer Simulations. Issue 20 (9th January 2018) - Uribe, Lalita; Diezemann, Gregor; Gauss, Jürgen; Morth, Jens Preben; Cascella, Michele
Abstract: We performed quantum‐chemical calculations, ab initio molecular dynamics, hybrid quantum mechanics/molecular mechanics (QM/MM) and enhanced sampling metadynamics simulations to investigate the origin of metal specificity in isatin hydrolase from Labrenzia aggregata . The peculiar octahedral binding geometry of the Mn 2+ ion in the Michaelis complex includes both the isatin substrate and the catalytic water within the first coordination shell of the cation. Our calculations show that the same arrangement of the ligands cannot be efficiently achieved in the presence of other small divalent metal cations such as Zn 2+ or Cu 2+ . On the contrary, bulkier alkaline‐earth cations such as Mg 2+, which allow octahedral coordination, are not able to activate the catalytic water into the stronger OH − nucleophile required to attack the stable N ‐aryl‐amide moiety of isatin. Abstract : The hydrolysis reaction of isatin in isatin hydrolase from Labrenzia aggregata is efficiently catalyzed only in the presence of Mn 2+, whereas other divalent metal cations are either not able to maintain the correct geometry of the Michaelis complex or cannot properly activate the reactants.